(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Banks are considered the main basis of financial sector ,so they must be submitted to sound and strict regulatory system and so as to ensure their operations and according to instructions and regulations , in order to maintain the integrity of the banking sector and financial sector in general .One of the importance regulatory tools that are adopted by the Iraqi Central Bank to control over the banks an financial and periodic statements that are provided by the banks in accordance with planned schedules .The financial statements of the banks must reflect clearly and accurately financial situation and the result of their activities during the period in which they represent to achiveing its purposes.So it has the goal of Search is statement role of the financial statements of banks in achieving the banking supervision of the Central Bank of Iraq, and that through the presentation of the theoretical framework for the banking supervision and financial statement of banks, has also been a survey of the views of a sample of the research community, represented by (Iraqi Central Bank, Industrial Bank, North Bank for Finance and Investment) using the method of statistical analysis to get to the results.It was chosen as the time period of 2007-2012 to look for changes witnessed by the banking supervision through the insertion of camel system and make amendments to somePeriodic statements models.The search to find a set of conclusions, including: development of supervisory oversight mechanism by sending the financial statements of banks electronically to the Central Bank of Iraq will make it more effective and confidential.The search Find a set of conclusions to including: interest to the insertion of electronic information systems and related to the delivery of financial statements to the Central Bank of Iraq from banks, helping to increase the efficiency and accuracy and confidentiality of the work.